Benefits of Golf Tourism to a Suburban Settlement: The Case of Ilara-Mokin in Ondo State, Nigeria - Emmanuel, Adebayo Adewunmi (European Journal of Multidisciplinary Studies, 2017)
Sports and associated facilities form a major tourist attraction and contribute to the development of host communities across the globe. This includes the benefits accruing from golf tourism to host settlements. This research focused on the benefits of Smokin Hills Golf Course which is located in a suburban settlement, Ilara-Mokin, in Ondo State, Nigeria. It investigated the benefits of the existence of the golf course to the community at large and to its residents. It equally obtained the negative sentiments of residents of the community about the existence of the golf course. Clustered and stratified sampling techniques were employed to obtain data from a purposive sample size of 150 residents in a culturally and economically homogenous Ilara-Mokin. A structured questionnaire and an interview guide were utilised to obtain relevant data from selected residents and the golf course officials. Among other findings, it was discovered that social benefits outweighed economic benefits accruing to the community while the economic benefits were dominated by sales of consumables such as foods, drinks and farm produce. Recommendations include further infrastructural development of the town and an improved wage for workers at the golf course as indicated by residents.
Keywords: benefits, golf course, sports, suburban settlement, tourism